Treatment of tequila distillation volatile residues by electrochemical oxidation using titanium electrodes - Martínez-Orozco, Edgardo (Environmental technology, 2024)
ABSTRACTTequila production occurs in Mexico's designated area of origin, principally in the Jalisco State. Its residues are a challenge in treatment and tracking due to a lack of technology, non-economic treatments available, low environmental consciousness and incipient control from authorities. In 2021, average production was close to 1.5 million tequila litres per day with an estimated residue yield of 10-12 litres of stillage (tequila vinasses) per tequila litre produced, including volatile fractions. This research aims to reduce organic matter by electrooxidation (EO) from 5 distillation volatile residual effluents (two-stage still distillation) from three tequila distilleries, first and second-stage heads and heads and tails and second-stage non-evaporated fraction. Round 3 mm titanium (grade-1) electrodes (one anode and one cathode) were used, with fixed voltage to a value of 30 VDC at 0, 3, 6, 9 and 12 h with 75 experiments. Gas chromatography was used to analyse methanol, ethanol, acetaldehyde, ethyl acetate, n-propanol, sec-butanol, iso-butanol, n-butanol, iso-amyl, n-amyl, and ethyl lactate content. Treatment shows positive results, reducing organic matter content in all effluents in a Chemical Oxygen Demand COD range of 580-1880 mg/L.h, particularly useful in the second-stage non-evaporated fraction for water recovery.HIGHLIGHTSResidual effluent treatment is beneficial to environmental and resource sustainability.Process without adding materials achieving cleaner treated effluents.Process aimed as the final step to recover water.This process could help the Tequila industry to reach a higher sustainability level by reducing water usage and untreated residues